Proteomic and bioinformatic analyses of proteins in the outer membrane and extracellular compartments and outer membrane vesicles of Candidatus Liberibacter species - Huang, Yixiao; Zhu, Fanchao; Koh, Jin; Stanton, Daniel; Chen, Sixue; Wang, Nian (Frontiers in Microbiology, 2022)
Citrus Huanglongbing (HLB) is the most devastating citrus disease in the world. Candidatus Liberibacter asiaticus (Las) is the prevalent HLB pathogen, which is yet to be cultivated. A recent study demonstrates that Las does not contain pathogenicity factors that are directly responsible for HLB symptoms. Instead, Las triggers systemic and chronic immune responses, representing a pathogen-triggered immune disease. Importantly, overproduction of reactive oxygen species (ROS) causes systemic cell death of phloem tissues, thus causing HLB symptoms. Because Las resides in the phloem tissues, it is expected that phloem cell might recognize outer membrane proteins, outer membrane vesicle (OMV) proteins and extracellular proteins of Las to contribute to the immune responses. Because Las has not been cultivated, we used Liberibacter crescens (Lcr) as a surrogate to identify proteins in the OM fraction , OMV proteins and extracellular proteins by liquid chromatography with tandem mass spectrometry (LC-MS/MS). We observed OMVs of Lcr under scanning electron microscope, representing the first experimental evidence that Liberibacter can deliver proteins to the extracellular compartment. In addition, we also further analyzed LC-MS/MS data using bioinformatic tools. Our study provides valuable information regarding the biology of Ca. Liberibacter species and identifies many putative proteins that may interact with host proteins in the phloem tissues.